2021
DOI: 10.1101/2021.04.30.21256240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Women’s views on accepting COVID-19 vaccination during and after pregnancy, and for their babies: A multi-methods study in the UK

Abstract: Background: COVID-19 vaccines are the cornerstone of the pandemic response and now advised for pregnant women in the United Kingdom (UK) however COVID-19 vaccine acceptance among pregnant women is unknown. Methods: An online survey and semi-structured interviews were used to investigate pregnant women's views on COVID-19 vaccine acceptability for themselves when pregnant, not pregnant and for their babies. 1,181 women, aged over 16 years, who had been pregnant since 23rd March 2020, were surveyed between 3rd… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 32 publications
1
35
0
4
Order By: Relevance
“…Our results showed that pregnant women of Afro-Caribbean ethnicity were less likely to receive the vaccine; this is consistent with recent questionnaire data both in pregnancy and outside of pregnancy. 8 However, people from ethnic minority groups are more likely to suffer from severe COVID-19, with increased risk of hospitalization, higher ICU admissions, and higher death rates in those of South Asian ethnicity in the United Kingdom. 19 Of note, ethnicity did not seem like an indication for COVID-19 vaccination in pregnancy until March 24, 2021, 12 emphasizing the importance of tailoring counseling to individual pregnant women to encourage uptake.…”
Section: Interpretation Of Study Findings and Comparison With The Published Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that pregnant women of Afro-Caribbean ethnicity were less likely to receive the vaccine; this is consistent with recent questionnaire data both in pregnancy and outside of pregnancy. 8 However, people from ethnic minority groups are more likely to suffer from severe COVID-19, with increased risk of hospitalization, higher ICU admissions, and higher death rates in those of South Asian ethnicity in the United Kingdom. 19 Of note, ethnicity did not seem like an indication for COVID-19 vaccination in pregnancy until March 24, 2021, 12 emphasizing the importance of tailoring counseling to individual pregnant women to encourage uptake.…”
Section: Interpretation Of Study Findings and Comparison With The Published Literaturementioning
confidence: 99%
“…Concerns were particularly related to long-term effects and about the speed at which vaccines were developed and tested. 8 There is additional evidence that pregnant women in the United Kingdom have concerns about vaccination in general. Although the United Kingdom has an extensive antenatal immunization program, with a routine offer of vaccination against pertussis, diphtheria, tetanus, polio, and seasonal influenza, 24 a multicenter questionnaire study into vaccine hesitancy for influenza and pertussis vaccination in pregnancy found that, most commonly, vaccination was declined for fear of adverse fetal effects.…”
Section: Obstetrics Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, es importante mencionar que en algunos estudios se ha encontrado que las mujeres embarazadas tenían menos predisposición a vacunarse que las mujeres no gestantes (Skirrow et al, 2021;Skjefte et al, 2021;Sutton et al, 2021). Esto probablemente se deba a que las mujeres gestantes no solo se preocupan de los efectos adversos de las vacunas en ellas, sino de la seguridad y el bienestar del nonato; siendo esto uno de los principales motivos por los que las mujeres gestantes tomarían la decisión de vacunarse o no (Geoghegan et al, 2021).…”
Section: Discussionunclassified
“…Por otro lado, una de las razones por las que no se vacunarían fue porque desconfiaban del sistema de salud, siendo esta desconfianza mayor en las gestantes. Otros estudios han reportado resultados similares, donde la confianza en las instituciones de salud y la información recibida por estas fueron importantes predictores para que las mujeres gestantes acepten la vacunación contra la COVID-19 (Levy et al, 2021;Skirrow et al, 2021;Skjefte et al, 2021). Este comportamiento también se ha visto en la población en general, en un estudio realizado en 19 países se encontró que, si una persona tenía mayor confianza en su gobierno, entonces era más probable que tuviera una actitud positiva hacia la vacunación, o también si algún miembro del personal de salud se lo recomendaba (Lazarus et al, 2021).…”
Section: Discussionunclassified